Audyt energetyczny, charakterystyka energetyczna oraz świadectwo charakterystyki energetycznej - co wiemy na ich temat? = Energy audit, energy performance and Energy Performance Certificate - what do we know about them? - Nakielska, Magdalena; Pawłowski, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The current state of law regarding the modernization and thermal protection of buildings consists of several regulations. Each of them refers to the energy intensity of buildings, but refers to another document. Three concepts related to energy consumption in a building: Energy Audit, Energy Performance of the building and Energy Performance Certificat of the building.
Keywords: audyt energetyczny; charakterystyka energetyczna; świadectwo charakterystyki energetycznej; energochłonność budynku; energy audit; energy performance; Energy Performance Certificate; energy consumption of the building